Hematopoietic stem cell transplantation from non‐sibling matched family donors for patients with thalassemia major in Jordan. (23rd October 2015) - Hussein, Ayad Ahmed; Al‐Zaben, Abdulhadi; Khattab, Eman; Haroun, Anas; Frangoul, Haydar
Abstract: There are limited data on the outcome of patients with thalassemia receiving HSCT from non‐sibling matched family donors. Of the 341 patients with thalassemia major that underwent donor search at our center from January 2003 to December 2011, 236 (69.2%) had fully matched family donor of which 28 patients (8.2%) had non‐sibling matched family donors identified. We report on seven patients with a median age of eight yr (4–21) who underwent myeloablative (n = 4) or RIC (n = 3) HSCT. The median age of the donors was 33 yr (4–47), three were parents, two first cousins, one paternal uncle, and one paternal aunt. All patients achieved primary neutrophil and platelet engraftment at a median of 18 (13–20) and 16 days (11–20), respectively. One patient developed grade II acute GVHD, and two patients developed limited chronic GVHD. One patient experienced secondary GF requiring a second transplant. At a median follow‐up of 69 months (7–110), all patients are alive and thalassemia free. Our data emphasize the need for extended family HLA typing for patients with thalassemia major in regions where there is high rate of consanguinity. Transplant from non‐sibling matched family donor can result in excellent outcome.